2022
DOI: 10.3390/biomedicines10112775
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting DNA Replication Stress as a Therapeutic Strategy for Breast Cancer

Abstract: Proliferating cells rely on DNA replication to ensure accurate genome duplication. Cancer cells, including breast cancer cells, exhibit elevated replication stress (RS) due to the uncontrolled oncogenic activation, loss of key tumor suppressors, and defects in the DNA repair machinery. This intrinsic vulnerability provides a great opportunity for therapeutic exploitation. An increasing number of drug candidates targeting RS in breast cancer are demonstrating promising efficacy in preclinical and early clinical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 142 publications
0
10
0
Order By: Relevance
“…Given its described function as a dNTPase, it has been mysterious why loss-of-function mutations in SAMHD1 are associated with AGS, SLE, oncogenesis, and chronic DNA damage in cells. ,,, Insight into this question was provided by two studies that revealed secondary DNA damage repair (DDR) functions of SAMHD1, that if inhibited, could lead to additional antitumor effects . One repair function of SAMHD1 is to promote homologous recombination by its association with double strand break (DSB) foci, , which helps explain the association of SAMHD1 with oncogenesis and DNA damage.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Given its described function as a dNTPase, it has been mysterious why loss-of-function mutations in SAMHD1 are associated with AGS, SLE, oncogenesis, and chronic DNA damage in cells. ,,, Insight into this question was provided by two studies that revealed secondary DNA damage repair (DDR) functions of SAMHD1, that if inhibited, could lead to additional antitumor effects . One repair function of SAMHD1 is to promote homologous recombination by its association with double strand break (DSB) foci, , which helps explain the association of SAMHD1 with oncogenesis and DNA damage.…”
mentioning
confidence: 99%
“… 5 , 11 , 13 , 18 Insight into this question was provided by two studies that revealed secondary DNA damage repair (DDR) functions of SAMHD1, that if inhibited, could lead to additional antitumor effects. 19 One repair function of SAMHD1 is to promote homologous recombination by its association with double strand break (DSB) foci, 20 , 21 which helps explain the association of SAMHD1 with oncogenesis and DNA damage. Another role for SAMHD1 is in coordinating the restart of stalled replication forks (RFs).…”
mentioning
confidence: 99%
“…Previous studies have shown that WDHD1 is closely related to the maintenance of genomic integrity and the DNA replication process, and genomic instability accelerates the acquisition of genetic diversity [ 76 ]. Meanwhile, the uncontrolled replication process provides tumor cells with an inexhaustible source of fuel [ 77 ]. They are both hallmarks of cancer and are closely associated with tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…The concept, when mutations beneficial to the tumor create a vulnerability to inactivation of targets which compensate for such alterations is known as synthetic lethality [9]. For example, RS can be further enhanced by chemotherapy drugs that lead to DNA damage by interfering with replication such as topoisomerase I and II inhibitors, alkylating agents and nucleoside metabolic inhibitors, and tumors that already have high levels of RS are more sensitive to these drugs [10]. Several key studies demonstrated that genetic inactivation of ATR leads to synthetic lethality in ATM or TP53 mutated tumors, paving the way to use of small-molecule ATR inhibitors (ATRi) [11,12].…”
Section: Introductionmentioning
confidence: 99%